Teaching ESL composition : - Ferris, Dana R. (Lawrence Erlbaum Associates, Publishers, 2005)
Teaching ESL composition: purpose, process, and practice aims to present pedagogical approaches to the teaching of ESL compo-sition in the framework of current theoretical perspectives on second language (L2) writing processes, practices, and writers. It should therefore appeal to at least four different audiences; Teacher-educators and graduate students in TESOL prepa-ration programs. In-service ESL and EFL instructors currently engaged in teaching writing and related literacy skills. Mainstream composition teachers who wish to learn more about meeting the diverse needs of ESL writers. Researchers involved in describing L2 writing and investi-gating ESL composition pedagogy